The Effect of Trailing Edge Profile Modifications to Fluid-Structure Interactions of a Vertical Axis Tidal Turbine Blade - Nu Rhahida Arini; Stephen R Turnock; Mingyi Tan (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Renewable energy has become an essential energy alternative since the continual depletion of non-renewable energy resources and increasing environmental issues. Tidal energy is a promising future renewable resource which can be extracted using a vertical axis tidal turbine. Since it was proposed, a tidal turbine performance requires improvements which can be obtained by a blade’s trailing edge modification. Modifying the blade’s trailing edge profile is confirmed to be one way to improve a turbine’s work. However, the influence of a trailing edge modifications on a vertical axis tidal turbine blade’s interaction with fluid has not been fully understood, thus the fluid induced vibration as the fluid behaviour working on a vertical axis tidal turbine blade has not been completely discovered. In this paper, 2D fluid-structure interactions of modified vertical axis tidal turbine blades are examined and modelled using OpenFOAM. Three different modified blade profiles are proposed: sharp, rounded, and blunt. The modified profiles are employed to an original NACA 0012 blade and their influences on a vertical axis tidal turbine blade interaction are observed. The result discovers the fluid behaviour and fluid-induced vibrations at all positions (represented by 12 positions) over one turbine’s cycle. The results demonstrate the frequency domain blade velocities and time domain blade displacements for all modified blades. The fluid behaviour around the blade is confirmed by pressure distribution plots over the blade’s upper and lower surfaces. The results show that the blunt profile provides less frequent vibrations due to a reducing vorticity in the downstream fluid regime. However, the vibration amplitude that occurs on the blunt blade is higher than those of rounded and sharp profiles. Based on this research, the blunt trailing edge profile appears to be more favourable to be applied and used for vertical axis tidal turbine blades.